Simply Alice - Naylor, Phyllis Reynolds (New York, New York Simon Pulse, 2002)
In her freshman year, fourteen-year-old Alice experiences changes and challenges with friends, family, and school activities, which leave her feeling better about herself than ever before.
Keywords: Interpersonal relations -- Fiction; Brothers and sisters -- Fiction; High schools -- Fiction; Schools -- Fiction; Theater -- Fiction